PENERAPAN TERAPI MUROTTAL UNTUK MENGATASI NYERI PADA PASIEN POST SECTIO CAESAREA DI RS BHAKTI WIRA TAMTAMA SEMARANG - Susilowati, Nike Susilowati; Hastuti, Witri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Sectio Caesarea (SC) is a way to deliver a fetus by making an incision in the uterine wall through the front wall of the abdomen. Sectio Caesarea is carried out to prevent the death of the fetus or mother due to dangers or complications that would occur if the mother gave birth vaginally. One of the distraction techniques for pain relief is Murottal Al-Quran therapy. One of the distraction techniques for pain relief is Murottal Al-Quran therapy. Murottal therapy can reduce pain, because it has a distraction effect in inhibiting pain perception. Objective: to describe the application of Murottal therapy to treat pain in post-section caesarean patients at Bhakti Wira Tamtama Hospital, Semarang. Method: using a descriptive method by describing nursing care for Post Sectio Caesarea Patients in the Dhalia Room RST Bhakti Wira Tamtama Semarang, using pre-test and post-test. The research was conducted on 21 – 23 December 2023. Results: After carrying out the Murottal Therapy intervention to treat pain, the results showed a reduction in pain in post-section caesarean patients. Conclusion: Murottal Therapy for Treating Pain can overcome the Pain of Post Sectio Caesarea Patients. Suggestion: It is hoped that Murottal Therapy to Overcome Pain can be used as an independent nursing intervention in reducing the pain of Post Sectio Caesarea Patients.